Effects of cryoprotective agents on osmotic tolerance limit of testicular interstitial cells - Олександр Пахомов; Євгеній Посохов; Наталя Волкова; Надія Чернобай; Галіна Божок (Біофізичний вісник)
Background: Cryopreservation is a multistep process, which includes stages affecting biological material mechanically, osmotically and toxically. The use of cryopreservation of biological materials is cost-effective and affording long-term storage at cryogenic temperatures. It also guarantees the stability of the genetic component of cells and reduced contamination of the biological material.